Hubungan Penggunaan Media Sosial dan Peran Teman Sebaya dengan Perilaku Seksual Remaja - Fitriyah, Nurul; Arneti, Arneti; Rahmi, Sania Lailatu; Kornelia, Kori; Khadijah, Siti (Jurnal Bidan Mandiri, 2025)
Adolescent sexual behavior is influenced by various factors, including the use of social media and the role of peers. Aim; To examine the association between social media use and peer influence with adolescent sexual behavior at SMA Negeri 1 Ampek Angkek in 2025. Method; This was an analytic quantitative study with a cross-sectional approach. The research population was 1,060 students of SMA Negeri 1 Ampek Angkek, with a sample of 100 respondents selected using cluster random sampling. Data was collected through questionnaires and analyzed univariately and bivariately with the Chi-Square test using SPSS 25. Results; The study showed that 74% of respondents exhibited positive sexual behavior, 69% frequently used social media, and 52% were influenced by peers. There was a significant relationship between social media use and adolescent sexual behavior (p=0.025), and a highly significant relationship between the role of peers and adolescent sexual behavior (p=0.000). Conclusion; Social media and peers play an important role in shaping adolescent sexual behavior. School-based interventions such as reproductive health education, peer counselor programs, and strengthening digital literacy are recommended. Further research is suggested to explore additional variables such as the role of the family and religiosity.